Toxicity of a novel therapeutic agent targeting mitochondrial complex I. Issue 5 (4th August 2015) - Low Wang, CC; Galinkin, JL; Hiatt, WR
Abstract : R118 is an experimental compound that completed preclinical development as a potential medical therapy for the exercise limitation in peripheral artery disease. Animal studies established that R118 provided partial and reversible mitochondrial complex I inhibition with consequent increases in adenosine monophosphate (AMP) kinase activation in liver and skeletal muscle. After demonstration of improved exercise performance in a mouse model and safety in rodent and primate models, a phase I trial was performed in 24 subjects randomized to R118 vs. placebo (5:1) in escalating doses. Plasma lactic acid levels were transiently elevated in 20% of subjects at the lowest dose and in 100% of subjects using a different formulation at the highest dose, which was associated with hospitalization in all subjects and severe metabolic acidosis requiring prolonged intubation in two subjects. Thus, inhibition of mitochondrial complex I with R118 resulted in severe lactic acidosis, representing unacceptable toxicity from this mechanism of action.